Study of the oxygen mass transfer in viscous fermentation systems - Patel, Nilesh (University of Ottawa (Canada), 2003)
During aerobic fermentations, availability of oxygen to microorganisms is a very important factor for their growth and subsequent product formation. To evaluate the amount of oxygen that is available to microorganisms for their consumption, the oxygen mass transfer coefficient (KLa ) is often used in the design and comparison of bioreactors. It becomes more difficult to characterize oxygen mass transfer and to design bioreactors when the viscosity of the medium constantly increases during the fermentation process. Therefore, this work is concerned with the study of K La in viscous fermentation systems. Two types of bioreactors, the reciprocating plate bioreactor and the stirred tank bioreactor, were used to study the growth of Aspergillus niger and the production of citric acid. This fermentation leads to a very viscous fermentation medium due to the long filamentous structure of Aspergillus niger. Before conducting fermentation experiments with the microorganism Aspergillus niger, wood pulp solutions were used as a model fluid to mimic its physical characteristics and to study the oxygen mass transfer in such mixtures. Experiments were done with different pulp concentrations and KLa was estimated using the gassing-out method. The estimated KLa values were then correlated to the power input per unit volume and the gas superficial velocity using a power law equation. Fermentation experiments with Aspergillus niger were conducted with both bioreactors at different agitation speeds, and KLa was estimated using a data reconciliation algorithm that used 12 measured process variables and 4 mass conservation models. KLa was obtained at different stages of fermentation and at different agitation intensities. It is believed that the data reconciliation algorithm allowed reliable estimates of KLa.
Keywords: Engineering, Chemical.